Pengambilan Keputusan Dalam Penggunaan Aplikasi Shopee Di Kalangan Mahasiswa Prodi Ekonomi Syariah Angkatan 2019 IAIN Sorong - Anita Ratna Kusuma; Rabiudin (At-Thariqah: Jurnal Ekonomi, 2024)
This study analyzes the factors that affect decision-making in the use of the Shopee application among students of the Sharia Economics Study Program class of 2019 at IAIN Sorong. This study uses a descriptive quantitative approach with a sample of 47 students selected through purposive sampling. Data collection was carried out through questionnaires and observations. The results of the study show that the factors of trust, security, service quality, convenience, and benefits affect students' decisions in using Shopee. The convenience factor was found to be the most dominant factor.